The Effect of (Think-Pair-Share) strategy on learning shot put In 8th grade students - Jabbar, Abdul Jaleel; Taha, Haider (Journal of Physical Education, 2018)
The Effect of (Think-Pair-Share) strategy on learning shot put In 8th grade students The problem of the research lies in turning physical education lesson into a recreational time only neglecting all its goals specially teaching sport skills. The research aimed at identifying the effect of using think, pair, and share strategy on learning shot put. The research hypotheses significant statistical differences between pre and posttests in the performance and the achievement of the experimental group. In addition to that, there are significant differences in the post tests of the experimental and control groups in shot put performance and achievement. The subject were (36) students. The researchers concluded that using think, pair and share strategy positively affects shot put performance. The researchers recommended that the strategy of "Think-Pair-Share" must be adopted as one of the most important strategies in learning motor skills in general.